An Error Analysis On The Use Of Simple Past Tense Among The Second Semester Students Majoring Food And Beverage Study Program At Balikpapan State Polytechnicin 2015-2016 - Abdul Gafur; Farida Farida (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2016)
The objectives of this study are (1) to identify and classify the errors of the Second Semester Students majoring Food and Beverage Study Program in Balikpapan State Polytechnic in using simple past tense, (2) to describe the frequency occurrence of the errors. The instrument used was a test on English simple past tense for high education level. The population of the study the Second Semester Students majoring Food and Beverage Study Program in Balikpapan State Polytechnic, which consisted of two classes. However, samples were used as the researcher could not cope with the whole population. The samples consisted of 50 students. Students errors identified in this study were categories into three types, namely, errors of omission errors addition and errors misformation. The result of the analysis shows that there were in all, 1234 errors among 50 students. The types of errors among the students in constructing and using English simple past tense consisted of 68 (5%) errors of omission, 95 (8%) errors of addition and 1071 (87%) errors of misformation. From the highest to the lowest, the errors were: misformation, addition, and omission. The average number of errors made of all the students was 46%. From the percentage, it can be concluded that the students’ mastery in using English simple past tense was poor.